SOLUTION OF FULLY Z-TRANSPORTATION PROBLEMS - A POORNIMA DEVI; Dr. G. VELAMMAL (Utilitas Mathematica, 2025)
In this paper, we present an innovative approach to solving the transportation problem with fully Z-number parameters (FZTP). First, we convert the FZTP to an FFTP with a certain reliability. Then the FFTP problem can be tackled by using additive inverse methods. This approach ensures that information regarding reliability is not lost.